Reward-based crowdfunding: a study of the entrepreneurs’ motivations when choosing the model as a venture capital alternative in Brazil - Amedomar, André (2018)
The main purpose of this study is to understand why Technology-Based Companies (TBCs) resort to reward-based crowdfunding as a financing alternative in Brazil over other alternatives that are already consolidated. In order to answer this question, we conducted a multiple-case study with four TBCs operating in different sectors and a platform hosting this type of campaigns. We found evidence that TBCs choose reward-based crowdfunding as a funding model because they are still in early stages of development, because they are after funds to finance specific projects and for motivations that do not directly involve raising funds. The findings corroborate the motivations mentioned in the literature and add new items.